The Admissibility of Testimonium De Auditu in Criminal Evidence: An Analysis of Decision Number 1361/Pid.B/2022/PN.Sby - Sinaga, Betrand (Justice Voice, 2025)
This study examines the juridical acceptance of testimonium de auditu testimony in criminal proceedings, as reflected in Decision Number 1361/Pid.B/2022/PN.Sby. The research concludes that the flexibility of judges in interpreting legal norms in evidence-gathering serves to achieve substantive justice. While Article 185 paragraph (1) of the Indonesian Criminal Procedure Code (KUHAP) requires direct firsthand experience for witnesses, the reality is that judges may still accept testimonium de auditu when supported by other relevant evidence that complements and strengthens the case’s narrative. This form of testimony has constitutional legitimacy as affirmed in Constitutional Court Decision Number 65/PUU-VIII/2010, which clarifies that indirect testimony is not automatically excluded, provided it is not the sole basis for a verdict and is corroborated by other evidence. This research supports the hypothesis that testimonium de auditu can be used as valid complementary evidence in certain cases, as long as it is within the boundaries of the legal system’s integrity and does not undermine the principles of fair trial and defendant rights. Furthermore, the study emphasizes the need for clearer guidelines in interpreting the admissibility of indirect testimony in Indonesian criminal procedure law.